Role Of Hydrostatic Outflow Vein Segment Dilatation In Av Fistula Maturation And Patency: An Intervention Cohort Study - Kumar, Surendra; Prabhakaran, Manoj; Khattri, Bhavya (Journal of Neonatal Surgery, 2025)
Introduction: Hemodialysis becomes pertinent for a major fraction of patients suffering from Chronic Renal Failure, in order to maintain homeostasis. Surgical Arteriovenous Fistula creation is an attempt to form an anastomotic site between a good-caliber artery and vein, maturing over time, offering a dilated aneurysmal site that can be easily cannulated to facilitate dialysis. Several surgical techniques have been put forth to improve the outcomes for such patients. The present study was done to assess the role of manual hydrostatic dilatation of outflow vein segment (draining vein) while creating AVF in its maturation and longevity of fistula patency. Material and methods: It was an intervention cohort study using convenience sampling recruiting 97 patients to undergo AVF creation in a tertiary heathcare setup. Subjects were randomized into two groups, ‘test’ group, who underwent AVF creation with manual hydrostatic dilatation of outflow venous segment, and controls where AVF was made using conventional surgical technique. Result: The primary outcome of immediate functioning of fistula was achieved in 90% of the test and in 96% of the control group. (p value = 0.251). In the test group, most participants had their first cannulation of AVF between 5th and 7th weeks. In contrast, the control group predominantly experienced their first cannulation later (6th to 8th week). The difference was found to be statistically significant (p value <0.001) and this highlighted the role of hydrostatic dilatation in achieving maturity of AVF early. Discussion & Conclusion: AVF lies at the heart of HD for CRF patients. Attempts have been made to cater needs for such patients for an ideal vascular access. Hydrostatic dilatation while during the AVF creation is a promising technique in order to achieve an early maturity of a well patent functioning fistula.